Liposomal retention : a fluorescence quantification approach. - Ng, Ching Siew. (2013)
This paper reviews results of experiments conducted to understand how the liposome permeability across the lipid bilayer is affected, after which liposome formulation with the best retention capabilities was achieved. Fluorescence spectrometry test was performed on liposome samples composed of 15:0 PC lipids which encapsulated 5(6)-Carboxy-fluorescein dye over a period of one month. The encapsulated dye serves as a marker for amount of content leakage over time.